Attention and Motor skill improvements in Mild Cognitive Impairment patients using COSMA Application - Aikaterini Christogianni; Kartheka Bojan; Elizabeta B. Mukaetova-Ladinska; VT. Sriramm; G. Murth; Gopukumar Kumarpilla (Serious Games Society, 2022)
Serious games have grown rapidly to provide cognitive stimulation for people with cognitive impairment. In this endeavour, we have created the COSMA games. In this two-arm study with patients with mild cognitive impairment (MCI), we investigated information processing speed and cognitive skills with 28 days of use of COSMA games, a brain stimulation gaming platform. We measured reaction times during neuropsychological assessment with the Cambridge Neuropsychological Test Automated Battery and the COSMA games. Results showed that people with MCI who played COSMA for 28 days at home were faster in 48% of the COSMA games and the Control group which played only during the laboratory visits was faster in 20% of the COSMA games at the end of the study.  Overall, these outcomes showed evidence that motor skill practice and learning retention are possible in people with MCI and that these skills are still able to improve with the regular practice of the COSMA games.